Stimulation of peroneal nerves reveals maintained somatosensory representation in transtibial amputees - Ritter, Caroline; Geisler, Maria; Blume, Kathrin R.; Nehrdich, Sandra; Hofmann, Gunther O.; Koehler, Hanna; Miltner, Wolfgang H. R.; Weiss, Thomas (Frontiers in Human Neuroscience, 2023)
Several studies have found changes in the organization of the primary somatosensory cortex (SI) after amputation. This SI reorganization was mainly investigated by stimulating neighboring areas to amputation. Unexpectedly, the somatosensory representation of the deafferented limb has rarely been directly tested. Here, we stimulated the truncated peroneal nerve in 24 unilateral transtibial amputees and 15 healthy controls. The stimulation intensity was adjusted to make the elicited percept comparable between both stimulation sides. Neural sources of the somatosensory evoked magnetic fields (SEF) to peroneal stimulation were localized in the contralateral foot/leg areas of SI in 19 patients and 14 healthy controls. Results demonstrate the activation of functionally preserved cortical representations of amputated lower limbs. None of the patients reported evoked phantom limb pain (PLP) during stimulation. Stimulation that evoked perceptions in the foot required stronger intensities on the amputated than on the intact side. Besides this, stronger stimulation intensities were required for amputees than healthy controls. Exploratorily, PLP intensity was neither associated with stimulation intensity nor dipole strength nor with differences in Euclidean distances (between SEF sources of the healthy peroneus and mirrored SEF sources of the truncated peroneus). Our results provide hope that the truncated nerve may be used to establish both motor control and somatosensory feedback via the nerve trunk when a permanently functional connection between nerve trunks and the prosthesis becomes available.